2022
DOI: 10.31083/j.rcm2301028
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, risk factors and prognosis of cardiovascular disease in the Coronavirus Disease 2019 (COVID-19) pandemic era: a systematic review

Abstract: Background: Since the emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) from China, the novel coronavirus disease 2019 (COVID-19) has caused more than five milion deaths worldwide. Several studies have elucidated the role of risk factors in the prognosis of cardiovascular disease (CVD) in the progression of COVID-19 pandemic. This systematic review assesses the link between COVID-19 and cardiovascular risk factors, and investigates the prognosis in the case of myocardial injury. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 63 publications
2
36
0
2
Order By: Relevance
“…In a study by Nieto-Garcia et al [ 24 ], diabetes mellitus and arterial hypertension were identified as the main associated comorbidities in patients with COVID-19 diagnosis and PIs, which corresponds with our findings. Another study confirms the same results that in patients with COVID-19 hypertension, diabetes mellitus, and obesity are associated with the number of ICU admissions and poor prognosis [ 26 ].…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…In a study by Nieto-Garcia et al [ 24 ], diabetes mellitus and arterial hypertension were identified as the main associated comorbidities in patients with COVID-19 diagnosis and PIs, which corresponds with our findings. Another study confirms the same results that in patients with COVID-19 hypertension, diabetes mellitus, and obesity are associated with the number of ICU admissions and poor prognosis [ 26 ].…”
Section: Resultssupporting
confidence: 77%
“…They identified HAPIs, Moisture-Associated Skin Damage (MASD), or Medical device-related pressure injuries (MDRPI) in 64% of 100 patients. The skin injuries were more frequently reported in patients supported with ECMO [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, during the COVID-19 pandemic era, safe distancing measures were adopted to curb the spreading of the virus, thus leading to the temporary cessation of many CR programs, the discontinuation of CR provision, and thus the further deterioration of CVD patients' cardiovascular function [15][16][17]. Furthermore, a recent systematic review found that CVD patients affected by COVID-19 presented worse outcomes and increased risk of morbidity, whereas COVID-19 itself also induced myocardial injury, arrhythmia, acute coronary syndrome, and venous thromboembolism [18].…”
Section: Introductionmentioning
confidence: 99%
“…We strongly agree to the authors’ assertion that the several barriers related to the underutilization of the traditional center-based CR programs can be addressed by the implementation of digital health interventions (DHIs) (Winnige et al (2021 2 )) Indeed, a recent critical review of ours has proclaimed the potential effective role of telehealth interventions as alternative sufficient methods of delivering CR during over demanding socioeconomic conditions, such is the ongoing COVID-19 pandemic (Stefanakis et al (2021 3 ), Pepera et al (2022 5 ))…”
mentioning
confidence: 99%